ANALISIS PENGARUH KUALITAS PELAYANAN DAN KUALITAS PRODUK TERHADAP MINAT BELI ULANG (Studi Kasus Pada Bengkel Kenteng Cak Rus Rembang (Potensio, 2012)
AbstractThe purpose of this study was to analyze the influence of customer service competence to service quality, technical competence influence on product quality, influence the quality of service and product quality to repurchase intension of customers on Haekal Tech workshop. The research sample of 100 respondents selected using purposive random sampling method. The collected data were then analyzed using simple linear regression and multiple linearregression. The results of this study indicate that there is a positive and significant impact the customer service competence on the service quality, technical competence on product quality, and the quality of service and product quality to repurchase intention. Keyword: customer service competence, technical competence, service quality, productquality, repurchases intention